2014
DOI: 10.1631/jzus.b1400157
|View full text |Cite
|
Sign up to set email alerts
|

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration

Abstract: Abstract:Six japonica rice genotypes, differing in panicle type, grain density, and phytic acid (PA) content, were applied to investigate the effect of grain position on the concentrations of major mineral nutrients and its relation to PA content and grain weight within a panicle. Grain position significantly affected the concentrations of the studied minerals in both the vertical and horizontal axes of a rice panicle. Heavy-weight grains, located on primary rachis and top rachis, generally had higher mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Studies showing high positive correlation of Zn with PA-P content (r = 0.5; <0.01) (Liang el al. 2007) to no correlation between PA and mineral elements (Su et al 2014;Perera et al 2019) have been reported earlier. The present study also revealed absence of significant correlation between the mineral micronutrients (Fe and Zn) and PA which is an indication that reduction of PA as well as increase in the Fe and Zn can be done simultaneously in breeding programs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Studies showing high positive correlation of Zn with PA-P content (r = 0.5; <0.01) (Liang el al. 2007) to no correlation between PA and mineral elements (Su et al 2014;Perera et al 2019) have been reported earlier. The present study also revealed absence of significant correlation between the mineral micronutrients (Fe and Zn) and PA which is an indication that reduction of PA as well as increase in the Fe and Zn can be done simultaneously in breeding programs.…”
Section: Discussionmentioning
confidence: 72%
“…The finding was comparable to Chinese japonica rice (6.9 to 10.3 g/kg; mean of 8.7 g/kg) and Korean rice (8.6 to 17.6 g/kg; mean of 12.6 g/kg) (Lee et al 1997;Liu et al 2005;Liang et al 2007). However, in six japonica rice genotypes showed variation for PA in BR ranging from 3.68 to 5.07 mg/g (Su et al 2014), whereas, three indica rice cultivars showed PA content from 3.99 mg/g to 7.34 mg/g (Wang et al 2011). More recently, variation in the PA contents of 69 WRC (World Rice Core collection) accessions found to be in the range of 8.24-17.41 mg/g (Perera et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Among the 24 japonica rice cultivars studied by Liu ( 2005 ), the PA content ranged from 0.68% for ‘Xiu 217’ to 1.03% for ‘Huai 9746’. Spikelet architecture changes panicle morphology that can cause grain PA variation in rice depending on the cultivar (Su et al 2014 ). The variation in PA-P content among 18 different rice cultivars grown in Tsukuba, Japan was evident in an experiment conducted using FACE technology (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…The molar ratio of PA/Fe is recommended to be 1 or lower for better Fe absorption from cereals when there are no enhancers for absorption (Hurrell and Egli 2010 ). In rice, grains in the primary rachis and upper rachises tend to have a lower molar ratio of PA/Zn relative to grains in the secondary rachis and lower rachises of the panicle, suggesting that grain position has an effect on Zn bioavailability (Su et al 2014 ). To develop rice with a higher micronutrient bioavailability, it is wise to consider the PA/micronutrient ratio and set the target as a high micronutrient content as well as a low-PA content.…”
Section: Reviewmentioning
confidence: 99%
“…Oat grains have been searched for years because of specific chemical composition, nutritional and physiological characteristics of the grains. Previous researchers working on wheat and paddy indicated that grain physical characteristics and chemical composition might vary based on the position of grain within spike or panicle (Boz et al, 2012;Su et al, 2014). The studies on physical and chemical characteristics of grains located at different sections of oat panicle are quite limited.…”
Section: Introductionmentioning
confidence: 99%